Lakon Bharatayuda dalam Tradisi Ruwahan Sajian Ki Cahyo Kuntadi - Sukesi Sukesi (Institut Seni Indonesia Surakarta, 2020)
The ruwahan tradition is a tradition that is, until now, believed by most Javanese people to send prayers as well as to resist disaster. Usually this tradition is carried out by wayang kulit performances with lakon Bharatayuda. It is said that this tradition had existed since 1921-1926 where this lakon is believed to resist the bubonic plague. This research is meant to see the tendency of lakon treatment by Cahyo Kuntadi based on the sanggit theory proposed by Sugeng Nugroho in viewing the sanggit lakon which consists of (1) the structure of lakon, (2) the study of intertextuality, (3) the characterizations, (4) Theme and Message. The method used is descriptive analytical method, namely by presenting the research results based on empirical data in the field. The results of this study indicate that there is an interpretation of lakon done by Cahyo Kuntadi in relation to the new performance media called virtual.